Insights into the Biosynthesis of Dehydroalanines in Goadsporin. Issue 3 (8th January 2016) - Ozaki, Taro; Kurokawa, Yukari; Hayashi, Shohei; Oku, Naoya; Asamizu, Shumpei; Igarashi, Yasuhiro; Onaka, Hiroyasu
Abstract: Dehydroalanines in goadsporin are proposed to be formed by GodF and GodG, which show slight homology to the N‐terminal glutamylation and C‐terminal elimination domains, respectively, of LanB, a class I lanthipeptide dehydratase. Although similar, separated‐type LanBs are conserved among thiopeptides and indispensable for their biosynthesis and biological activities, these enzymes had not yet been characterized. Here, we identified goadsporin B, which has unmodified Ser4 and Ser14, from both godF and godG disruptants. The godG disruptant also produced goadsporin C, a glutamylated‐Ser4 variant of goadsporin B. These results suggested that dehydroalanines are formed by glutamylation and glutamate elimination. NMR analysis revealed for the first time that the glutamyl group was attached to a serine via an ester bond, by the catalysis of LanB‐type enzymes. Our findings provide insights into the function of separated‐type LanBs involved in the biosynthesis of goadsporin and thiopeptides. Abstract : A clear route : The pathway of goadsporin biosynthesis is proposed following inactivation of the genes for azole and dehydroalanine formation. Notably, this study provides an insight into the structure of the glutamylated inter‐ mediate in the catalysis of LanB‐type enzymes.